Epidermal growth factor receptor as an early diagnostic marker of oral squamous cell carcinoma: Marking the line between severe dysplasia and oral squamous cell carcinoma - Sankeerti Mala (Wolters Kluwer Medknow Publications, 2019)
Context: Epidermal growth factor receptor (EGFR) and its ligands are involved in the cell growth of 70% cancer cells. EGFR overexpression or dysregulation may alter intracellular signaling pathways that affect tumor cell survival and apoptosis. It is hypothesized that only those potentially malignant lesions express high levels of EGFR progress to frank malignancies during tumorigenesis which suggests that increase in receptors might be the cause of malignancy rather than the effect of malignancy. Aims: The aim of the study was to assess and correlate the expression of EGFR in varying grades of oral epithelial dysplasia, oral squamous cell carcinoma (OSCC), and normal oral mucosa and to evaluate the early rate of malignant transformation in potentially malignant lesions. Settings and Design: It was a immunohistochemical study. Subjects and Methods: Twenty formalin-fixed, paraffin-embedded blocks of various grades of oral epithelial dysplasia, 10 formalin-fixed, paraffin-embedded blocks of OSCC, and 10 normal mucosae are stained with routine hematoxylin and eosin and immunostained with EGFR by avidin-biotin method. Statistical Analysis Used: Statistical analysis was performed by one-way ANOVA and multiple comparison tests using IBM SPSS Software 20.0 20. Results: Of 40 cases analyszd, 38 cases showed EGFR expression with varied extent and intensity of staining in the cytoplasm and cell membrane of keratinocytes in basal, parabasal, deep spinous, and superficial spinous layer. The results showed a statistically significant increase (P < 0.0001) in the staining extent and intensity of EGFR expression in severe dysplasia and OSCC. Conclusions: EGFRs may act as a marker since they reflect the early changes in dysplastic lesions - predicting the rate of malignant transformation in potentially malignant disorders and thereby aiding the oral pathologist in arresting the lesion before it enters malignancy.